Neutron capture data for unstable nuclei – Astrophysical quests and experimental challenges - Käppeler, F. (HNPS Advances in Nuclear Physics, 2019)
The abundances of the chemical elements heavier than iron can be attributed in about equal parts to the r and s processes, which are taking place in supernova explosions and during the He and C burning phases of stellar evolution, respectively. So far, quantitative studies of the r-process are out of reach, because it involves reactions on extremely short-lived neutron-rich nuclei. On the contrary, the situation for the s-process is far advanced, thanks to a comprehensive database of experimental (n,γ) cross sections for most isotopes along the reaction path from 12C to the Pb/Bi region. For the stable isotopes last gaps in the data are presently closed, but further studies are clearly needed to reach the required accuracy and to resolve remaining discrepancies. The quest for cross sections of unstable isotopes remains a persisting challenge though. In particular, nuclei which act as branching points are of prime interest, because they provide key information on the deep stellar interior. While the activation method is limited to a few exceptional branch-point nuclei, successful measurements via the time-of- flight technique are depending on intense pulsed neutron sources and elaborate methods for sample production. Current developments in Europe are providing promising perspectives in both areas.